An overview assessment of the revised draft WTO modalities for agriculture - Gifford, Mike; Montemayor, Raul (International Centre for Trade and Sustainable Development, 2008)
The revised draft modalities text issued by the Chair of the WTO agricultural negotiating group on February 8, 2008, reflects the considerable incremental progress which has been made in elaborating, clarifying and putting into legal language the first draft of July 2007. However, there are still a large number of issues which remain open and which will need to be narrowed down further by senior officials before ministers can be asked to resolve the most politically sensitive. The Chair has suggested half a dozen to a dozen issues are about the maximum ministers could be realistically asked to settle. This paper provides an overview assessment of the implications of the revised modalities text in terms of its ambition and balance as viewed from the perspective of both developed and developing countries, and identifies the key issues that will likely require ministerial decisions. It goes on to examine what additional issues could be added as part of a final deal once there is agreement on modalities and there is an assessment of the ensuing draft schedules. It concludes by venturing some views on the likely trade-offs between agriculture and other parts of the Doha negotiations, particularly the non-agricultural market access (NAMA) negotiations. This assessment draws from and builds on the complementary detailed analysis which has been undertaken on the implications of the new draft modalities text for four major Doha participants - the US, EU, Brazil and India.